Virtual-Physical Integration for Intelligent Engineering Investment Teaching in Finance and Economics Universities - Quan Mao (Ilmu Inovasi Nusantara, 2026)
A major challenge in engineering management education at finance and economics universities is the limited depth of students’ engineering and technological foundations, even as the demand for decision-making competence in complex practical scenarios continues to grow. This condition requires a practical teaching model that can effectively connect technical understanding, decision simulation, and managerial integration. This study aims to develop and evaluate a practical teaching model for intelligent engineering investment that integrates virtual simulation and physical experimentation within the Engineering Management Program at Central University of Finance and Economics. The study employed a controlled experimental design by dividing students into three groups: a virtual simulation-based learning group, a physical experiment group, and a combined virtual-physical learning group. Evaluation was conducted using multidimensional questionnaires covering knowledge construction, skill development, cognitive experience, innovation capability, and teaching feedback. The data were analyzed using Analysis of Variance to identify differences in effectiveness among the teaching models. The findings indicate that the integrated virtual-physical model achieved superior outcomes compared with single-mode approaches across all assessed dimensions. Physical experimentation strengthened students’ foundational understanding and concrete technical comprehension, whereas virtual simulation supported the exploration of complexity, dynamic scenarios, and management-based decision-making. The implications of this study suggest that the integration of physical experimentation and virtual simulation can serve as an operational paradigm for reforming engineering practice education, particularly in finance and economics institutions that require a balanced development of technological competence, investment analysis, and managerial decision-making capability in response to the demands of new infrastructure initiatives and emerging engineering education